THE CHALLENGE OF LABOUR SHORTAGE FOR SUSTAINABLE CONSTRUCTION - Mohd Rahim, Faizul Azli; Mohd Yusoff, Nurul Safwah; Chen, Wang; Zainon, Nurshuhada; Yusoff, Sumiani; Deraman, Rafikullah (PLANNING MALAYSIA, 2016)
In line with the principle of sustainable development, construction projects ought to be developed to bring benefits across all aspects, namely economic, social, and environmental. One the other hand, being a complex, fragmented and schedule driven industry, construction projects are frequently subject to problems that constrain their execution. Since construction is a labour intensive industry, the shortage of labour has become the crucial risks that hindering the construction project in achieving sustainability. This paper, in reviewing the concept of sustainable construction, also addresses the influential factors concerning the labour shortages in the construction industry and discusses how these challenges can be managed in producing sustainable construction labours.